Development of sugar- and fat-reduced pulse cookies with improved predicted glycemic behavior - Xinying Suo; Marianna Tagliasco; Matteo Bonfini; Laura Bonfili; Oscar Moreno Araiza; Anna Baggio; Anna Maria Eleuteri; Nicoletta Pellegrini; Elena Vittadini (Applied Food Research)
Cookies, a trendy snack, are traditionally characterized by a poor nutritional profile (high sugars and fats, low protein and fiber). To improve their nutritional profile, standard wheat “pasta-frolla” cookies were reformulated with 100 % pulse flour (chickpea and lentil), partial sugar reduction with a commercial fiber syrup (Meltec®), and full butter replacement using a structured fiber-sunflower oil-water emulsion (alone or in conjunction). Developed cookies had higher protein and fiber contents, reduced sugar (∼45 - 50 % reduction), and saturated fats (∼77 - 80 % reduction) and also had a lower predicted glycemic index compared to traditional cookies. Water activity and moisture content of the cookies were in line with those of the same product category, while they had a harder texture compared to their full butter counterparts due to the full substitution of butter (alone or in combination with sugar reduction). Lentil cookies showed slightly lower in vitro starch and remarkably higher protein digestibility than the control cookie, and the simultaneous application of sugar and fat substitution did not negatively affect their overall acceptability. The developed products are expected to be a suitable base for the development of snacks for elderly consumers, who are the population niche that, due to health issues, is most likely to be interested in this type of cookies.